Imagined cities : urban experience and the language of the novel - Alter, Robert (Yale University Press, 2005)
A literary investigation of how the modern metropolis--intoxicating, disturbing, powerful--changed perceptions and irrevocably altered the Western imagination. Alter traces the arc of literary development triggered by the runaway growth of urban centers from the early nineteenth century through the first two decades of the twentieth. As new technologies and arrangements of public and private space changed the ways people experienced time and space, the urban panorama became less coherent--a metropolis defying traditional representation and definition, a vast jumble of shifting fragments and glimpses--and writers were compelled to create new methods for conveying the experience of the city. In interpretations of novels by Flaubert, Dickens, Bely, Woolf, Joyce, and Kafka, Alter reveals the ways the city entered the literary imagination.--From publisher description.